The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1152/ajplung.00179.2011
|View full text |Cite
|
Sign up to set email alerts
|

Lung endothelial cell platelet-activating factor production and inflammatory cell adherence are increased in response to cigarette smoke component exposure

Abstract: An early event in the pathogenesis of emphysema is the development of inflammation associated with accumulation of polymorphonuclear leukocytes (PMN) in small airways, and inflammatory cell recruitment from the circulation involves migration across endothelial and epithelial cell barriers. Platelet-activating factor (PAF) promotes transendothelial migration in several vascular beds, and we postulated that increased PAF production in the airways of smokers might enhance inflammatory cell recruitment and exacerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…19,43,44 In this current study, we were able to confirm that PAFR is important for the inflammatory process, not only contributing to chemotaxis, but also activating innate and adaptive immune responses. PAF and its receptor have been widely linked to inflammation, 27,[45][46][47][48] and is interesting to highlight that not only immune cells, but also a great variety of cell types, from different organs, show an increase in inflammatory signaling as a response to PAF, for example, activating NF-kB, promoting superoxide …”
Section: Discussionmentioning
confidence: 99%
“…19,43,44 In this current study, we were able to confirm that PAFR is important for the inflammatory process, not only contributing to chemotaxis, but also activating innate and adaptive immune responses. PAF and its receptor have been widely linked to inflammation, 27,[45][46][47][48] and is interesting to highlight that not only immune cells, but also a great variety of cell types, from different organs, show an increase in inflammatory signaling as a response to PAF, for example, activating NF-kB, promoting superoxide …”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al (109) found that CSE inhibits platelet-activating factor (PAF) acetylhydrolase activity, which enhances PAF production and PMN adherence. Similarly, Meyer et al (83) showed that the expression of secretory leukoprotease inhibitor (SLPI) is regulated by Stat1, and both are increased in nasal epithelial cells and BALF of smokers, indicating that altered SLPI regulation and activity induced by CS could play a role in the development of respiratory inflammation and infection.…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 99%
“…Our previous in vitro studies indicated that iPLA 2 ␤ is critical for recruiting inflammatory cells to the endothe-lium via the production of PAF (4,6). Thus, we measured PAF production and the expression of adhesion molecules in cardiac endothelial cells isolated from WT and iPLA 2 ␤-KO mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has previously demonstrated increased expression of platelet-activating factor (PAF), in addition to the upregulation of adhesion molecules, in human coronary artery endothelial cells (HCAECs) acutely infected with T. cruzi (4). The role of PAF in the recruitment, transmigration, and activation of inflammatory cells is well established (5)(6)(7)(8).…”
mentioning
confidence: 99%